2007
DOI: 10.1093/aje/kwm098
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Birth Weight with Developmental Trends in Blood Pressure from Childhood through Mid-Adulthood: The Bogalusa Heart Study

Abstract: Low birth weight has been found to be associated with cardiovascular mortality and morbidity and with an adverse profile of several cardiovascular risk factors. The inverse association between birth weight and blood pressure was consistently reported from many populations. Using longitudinal data from the Bogalusa Heart Study (Louisiana), the authors investigated the association between birth weight and progression of blood pressure through early adulthood, comparing that relation between African Americans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…The presence of cardiovascular risk factors in childhood has been shown to track into adulthood, where their effects may be amplified. 39,40 This supports the concept that microvascular abnormalities in childhood track into adulthood, where they may predispose to hypertension and other adult conditions. Narrower arterioles detected from retinal photographs could indicate the presence of more generalized vessel changes, such as vasoconstriction or arteriosclerosis (medial hyperplasia and mural thickening) possibly related to endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 68%
“…The presence of cardiovascular risk factors in childhood has been shown to track into adulthood, where their effects may be amplified. 39,40 This supports the concept that microvascular abnormalities in childhood track into adulthood, where they may predispose to hypertension and other adult conditions. Narrower arterioles detected from retinal photographs could indicate the presence of more generalized vessel changes, such as vasoconstriction or arteriosclerosis (medial hyperplasia and mural thickening) possibly related to endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 68%
“…For example, it is speculated that malnutrition is an important factor, as observed in the finding that the prevalence of hypertension in children from Pakistan, who have alower BMI, is higher than that in children from the United States, who are predominantly overweight. 17 this is also supported by Mzayek et al, 18 who found an inverse association between birth weight and later blood pressure. In our study, the prevalence of hypertension was 10.5% in the underweight group.…”
Section: Discussionsupporting
confidence: 65%
“…19 Previous work in the Bogalusa Heart Study found that lower birthweight was associated with higher systolic blood pressure, triglycerides, insulin resistance, and low-density lipoprotein-cholesterol (LDL-C), and that the last three associations were stronger in blacks. 20,21 Frontini et al found more negative trends in cardiovascular risk factors among children and adolescents born < 10 th birthweight percentile for gestational age. 22 The aims of the current analysis were to examine whether there was a relationship between birthweight and metabolic syndrome as a whole (using multiple definitions of metabolic syndrome) as an adult in an AfricanAmerican/white cohort and to determine whether this relationship varied by body size.…”
mentioning
confidence: 99%